Potential impacts of future land use and climate change on the red List status of hthe Proteaceae in the Cape floristic region, south africa - (:unkn) unknown (My University, 2005)
Using spatial predictions of future threats to biodiversity, we assessed for the first time the relative potential impacts of future land use and climate change on the threat status of plant species. We thus estimated how many taxa could be affected by future threats that are usually not included in current IUCN Red List assessments. Here, we computed the Red List status including future threats of 227 Proteaceae taxa endemic to the Cape Floristic Region, South Africa, and compared this with their Red List status excluding future threats. We developed eight different land use and climate change scenarios for the year 2020, providing a range of best- to worst-case scenarios. Four scenarios include only the effects of future land use change, while the other four also include the impacts of projected anthropogenic climate change (HadCM2 IS92a GGa), using niche-based models. Up to a third of the 227 Proteaceae taxa are uplisted (become more threatened) by up to three threat categories if future threats as predicted for 2020 are included, and the proportion of threatened Proteaceae taxa rises on average by 9% (range 2–16%), depending on the scenario. With increasing severity of the scenarios, the proportion of Critically Endangered taxa increases from about 1% to 7% and almost 2% of the 227 Proteaceae taxa become Extinct because of climate change. Overall, climate change has the most severe effects on the Proteaceae, but land use change also severely affects some taxa. Most of the threatened taxa occur in low-lying coastal areas, but the proportion of threatened taxa changes considerably in inland mountain areas if future threats are included. Our approach gives important insights into how, where and when future threats could affect species persistence and can in a sense be seen as a test of the value of planned interventions for conservation.
Keywords: African Research